Impact of onychomycosis on the quality of life of patients - Fayrouz Debbagh; Fatima Babokh; Mohamed Sbai; El mostafa El mezouari; Redouane Moutaj (Mazandaran University of Medical Sciences, 2023)
Background and Purpose: Onychomycosis is a very common cosmopolitan onychopathy. It affects the fingers and toes, which are important organs of function and socialization. They can cause physical and psychological discomfort. The aim of this study was to assess the impact of onychomycosis on patients' quality of life.Materials and Methods: This is a prospective, cross-sectional, observational study carried out in the parasitology-mycology laboratory at the Avicenne Military Hospital in Marrakesh, over a 4-month period between June and October 2022, including all patients referred to the laboratory for mycological examination of a nail lesion suspected of onychomycosis of the hands and/or feet. Results: Onychomycosis was confirmed in 50 patients. Pain, nail thickening, and dyschromia were the most commonly reported symptoms (56%). Onychomycosis had an impact on at least one of the socio-economic, emotional, or functional aspects of affected patients' lives. More than half (56%) of participants felt embarrassed by the appearance of their nails; 40% hid them, and 28% had a complex about them. The functional aspect was the most bothersome, and concerned the time spent on nail care (56%), as well as the discomfort reported when wearing shoes (40%). Women were more worried about the need to hide their nails. A duration of onychomycosis evolution of over 5 years was associated with the highest response rate to questionnaires (66%).Conclusion: Although onychomycosis is not a fatal pathology, it significantly reduces the quality of life of affected patients. There is a need to raise the level of awareness of the general population and, above all, of the medical profession to ensure comprehensive management of onychomycosis.